Comparison of Efficacy of Intravenous Dexmedetomidine Versus Intravenous Lidocaine for Attenuation of Stress Response to Laryngoscopy and Endotracheal Intubation in Patients Undergoing General Anesthesia for Elective Surgeries: Dexmedetomidine Versus Lidocaine for Stress Response Attenuation - Syed, Yashal; Ali, Sheikh Ziarat; Chaudhry, Mehtab Tipu; Ahmad, Samra; Iram, Aqsa; Nemat, Tahira (Pakistan Journal of Health Sciences, 2025)
Harfaoui W, Alilou M, El Adib AR, Zidouh S, Zentar A, Lekehal B, et al. Patient Safety in Anesthesiology: Progress, Challenges, and Prospects. Cureus. 2024 Sep; 16(9). doi: 10.7759/cureus.69540. Wang Y, Wang J, Ye X, Xia R, Ran R, Wu Y, et al. Anaesthesia-Related Mortality Within 24 h Following 9,391,669 Anesthetics in Ten Cities in Hubei Province, China: A Serial Cross-Sectional Study. The Lancet Regional Health Western Pacific. 2023 Aug; 37. doi: 10.1016/j.lanwpc.2023.100787. Schiff JH, Wagner S. Anesthesia Related Mortality? A National and International Overview. Trends in Anesthesia and Critical Care. 2016 Sep; 9: 43-8. doi: 10.1016/j.tacc.2016.07.001. Kampman JM, Hermanides J, Hollmann MW, Gilhuis CN, Bloem WA, Schraag S, et al. Mortality and Morbidity After Total Intravenous Anaesthesia Versus Inhalational Anaesthesia: A Systematic Review and Meta-Analysis. EClinicalMedicine. 2024 Jun; 72. doi: 10.1016/j.eclinm.2024.102636. Sachidananda R, Umesh G. A Review of Hemodynamic Response to the Use of Different Types of Laryngoscopes. Anesthesia, Pain and Intensive Care. 2019 Jan; 24: 201-8. Brodsky MB, Akst LM, Jedlanek E, Pandian V, Blackford B, Price C, et al. Laryngeal Injury and Upper Airway Symptoms After Endotracheal Intubation During Surgery: A Systematic Review and Meta-Analysis. Anesthesia and Analgesia. 2021 Apr; 132(4): 1023-32. Hou H, Wu S, Qiu Y, Song F, Deng L. The Effects of Morning and Afternoon Surgeries on the Early Postoperative Sleep Quality of Patients Undergoing General Anesthesia. BMC Anesthesiology. 2022 Sep; 22(1): 286. doi: 10.1186/s12871-022-01828-w. Izzi A, Mincolelli G, D’Onofrio G, Marchello V, Manuali A, Icolaro N, et al. Awake Craniotomy in Conscious Sedation: The Role of A2 Agonists. Brain Sciences. 2024 Jan; 14(2): 147. doi: 10.3390/brainsci14020147. Saxena S, Marino L, Hammer B, Bilotta F, Berger-Estilita J. Peripheral Cytokine Modulation by Anesthetic Agents: A Systematic Review of Neuroprotective and Anti-Inflammatory Effects in Randomised Clinical Trials. Biomarkers. 2025 Jun; 23(just-accepted): 1-8. doi: 10.1080/1354750X.2025.2522891. Reshma BM. A Comparative Evaluation of Nebulized and Intravenous Dexmedetomidine on Attenuation of Hemodynamic Response to Laryngoscopy. Gupta M, Rohilla R, Gupta P, Tamilchelvan H, Joshi U, Kanwat J, et al. Nebulized Dexmedetomidine for Attenuating Hemodynamic Response to Laryngoscopy and Endotracheal Intubation in Adult Patients Undergoing Surgeries Under General Anesthesia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. BMC Anesthesiology. 2023 Dec; 23(1): 406. doi: 10.1186/s12871-023-02366-9. Seangrung R, Pasutharnchat K, Injampa S, Kumdang S, Komonhirun R. Comparison of the Hemodynamic Response of Dexmedetomidine Versus Additional Intravenous Lidocaine with Propofol During Tracheal Intubation: A Randomized Controlled Study. BMC Anesthesiology. 2021 Oct; 21(1): 265. doi: 10.1186/s12871-021-01484-6. Purohit A, Kumar M, Kumar N, Bindra A, Pathak S, Yadav A, et al. Comparison Between Dexmedetomidine and Lidocaine for Attenuation of Cough Response During Tracheal Extubation: A Systematic Review and Meta-Analysis. Indian Journal of Anesthesia. 2024 May; 68(5): 415-25. doi: 10.4103/ija.ija_790_23. Singh G, Kaur H, Aggarwal S, Sharda G, Jha A, Aggarwal H, et al. Intravenous Dexmedetomidine Versus Lignocaine in Attenuating the Hemodynamic Responses During Laryngoscopy and Endotracheal Intubation: A Randomized Double-Blind Study. Anesthesia, Pain and Intensive Care. 2019 Jan; 24: 181-6. Nand R, Feroz SH, Ahmed MS, Jafri SSultan M, Ahmed N, et al. Comparison of the Efficacy of Intravenous Lignocaine and Intravenous Dexmedetomidine in Attenuation of Hemodynamic Stress Response to Laryngoscopy and Endotracheal Intubation. Methodology. 2020 Apr. Mahjoubifard M, Heidari M, Dahmardeh M, Mirtajani SB, Jahangirifard A. Comparison of Dexmedetomidine, Lidocaine, and Fentanyl in Attenuation of Hemodynamic Response of Laryngoscopy and Intubation in Patients Undergoing Cardiac Surgery. Anesthesiology Research and Practice. 2020; 2020(1): 4814037. doi: 10.1155/2020/4814037. Gulabani M, Gurha P, Dass P, Kulshreshtha N. Comparative Analysis of Efficacy of Lignocaine 1.5 mg/kg and Two Different Doses of Dexmedetomidine (0.5 μg/kg and 1 μg/kg) in Attenuating the Hemodynamic Pressure Response to Laryngoscopy and Intubation. Anesthesia Essays and Research. 2015 Jan; 9(1): 5-14. doi: 10.4103/0259-1162.150167. Shrivastava P, Kumar M, Verma S, Sharma R, Kumar R, Ranjan R, et al. Evaluation of Nebulized Dexmedetomidine Given Pre-Operatively to Attenuate Hemodynamic Response to Laryngoscopy and Endotracheal Intubation: A Randomized Control Trial. Cureus. 2022 May; 14(5). doi: 10.7759/cureus.25223. De Cassai A, Sella N, Geraldini F, Zarantonello F, Pettenuzzo T, Pasin L, et al. Preoperative Dexmedetomidine and Intraoperative Bradycardia in Laparoscopic Cholecystectomy: A Meta-Analysis with Trial Sequential Analysis. Korean Journal of Anesthesiology. 2022 Jan; 75(3): 245-54. doi: 10.4097/kja.21359. Hung TY, Lin YC, Wang YL, Lin MC. Efficacy and Safety of Intravenous Dexmedetomidine as an Adjuvant to General Anesthesia in Gynecological Surgeries: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Taiwanese Journal of Obstetrics and Gynecology. 2023 Mar; 62(2): 239-51. doi: 10.1016/j.tjog.2022.11.010.